2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610486
|View full text |Cite
|
Sign up to set email alerts
|

A novel biometric authentication approach using electrocardiogram signals

Abstract: In this work, we present a novel biometric authentication approach based on combination of AC/DCT features, MFCC features, and QRS beat information of the ECG signals. The proposed approach is tested on a subset of 30 subjects selected from the PTB database. This subset consists of 13 healthy and 17 non-healthy subjects who have two ECG records. The proposed biometric authentication approach achieves average frame recognition rate of %97.31 on the selected subset. Our experimental results imply that the frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…To evaluate the performance of the proposed ECG system on the two databases, ten-fold cross-validation approach was used, which divided the total ECG images into ten equal parts, nine out of ten parts were used for training and the remaining were used for testing. In terms of authentication accuracies, we used internal fusions by addition and by concatenation respectively, and then compared our algorithm with previous authentication algorithms [36]- [39]. To the best of our knowledge, there are only two recent works on ECG authentication based on deep learning [40], [41], thus our study should be considered one of the first studies to build an ECG authentication system based on deep learning.…”
Section: Ecg Authenticationmentioning
confidence: 99%
“…To evaluate the performance of the proposed ECG system on the two databases, ten-fold cross-validation approach was used, which divided the total ECG images into ten equal parts, nine out of ten parts were used for training and the remaining were used for testing. In terms of authentication accuracies, we used internal fusions by addition and by concatenation respectively, and then compared our algorithm with previous authentication algorithms [36]- [39]. To the best of our knowledge, there are only two recent works on ECG authentication based on deep learning [40], [41], thus our study should be considered one of the first studies to build an ECG authentication system based on deep learning.…”
Section: Ecg Authenticationmentioning
confidence: 99%
“…Experiments demonstrated that the features extracted from one lead can be used to identify a person with 98% accuracy. To date, ECG has seen significant attention in biometric recognition studies [8,25,34,54], using both fiducial (specific anchor points such as P-QRST) and non-fiducial features. Despite the research efforts directed at ECG biometrics, at present there is only one commercial system available which exploits ECG or EMG biometrics for recognition, the B-secure [28].…”
Section: Related Workmentioning
confidence: 99%
“…Until now, one of the most popular strategies is fusion modalities. Thus, methods based on score fusion have achieved remarkable performance, most of which fuses two modalities [11,25,34]. As for ECG with the conventional biometric, there are fewer studies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Gurkan et al . [ 18 ] were used a combination of 20 AC/DCT features and 13 Mel-frequency cepstral coefficient features. In addition, information of the QRS complex have been considered as the third feature set using 120 samples of ECG signal around the R-peak (60 samples each side of R-peak).…”
Section: Introductionmentioning
confidence: 99%